2014
DOI: 10.1002/jcu.22195
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐enhanced endoscopic ultrasonography can predict a higher malignant potential of gastrointestinal stromal tumors by visualizing large newly formed vessels

Abstract: Intratumoral vessels observed in GISTs on CE-EUS are correlated with a higher degree of angiogenesis, resulting in higher malignant potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 36 publications
(50 reference statements)
0
48
0
Order By: Relevance
“…GIST was initially a purely descriptive term coined in 1983 by Mazur and Clark to define intra-abdominal tumors that were definitely not carcinomas [2, 3]. GISTs account for about 80% of gastrointestinal sarcomas, with a mean annual incidence of 10-15 per million [4, 5]. Nearly 50-70% of the clinically apparent tumors arise in the stomach, 20-30% arise in the small intestine, 5-15% in the large intestine, and less than 5% in other locations [6].…”
Section: Introductionmentioning
confidence: 99%
“…GIST was initially a purely descriptive term coined in 1983 by Mazur and Clark to define intra-abdominal tumors that were definitely not carcinomas [2, 3]. GISTs account for about 80% of gastrointestinal sarcomas, with a mean annual incidence of 10-15 per million [4, 5]. Nearly 50-70% of the clinically apparent tumors arise in the stomach, 20-30% arise in the small intestine, 5-15% in the large intestine, and less than 5% in other locations [6].…”
Section: Introductionmentioning
confidence: 99%
“…CEUS and CH-EUS have been evaluated in three series that sought to determine the malignancy potential of GISTs. [111216]…”
Section: Assessment Of the Malignant Potential Of The Gastrointestinamentioning
confidence: 99%
“…In the series of Yamashita et al ., 13 patients with GISTs underwent presurgical CH-EUS. [12] The analysis of the intratumoral vessels on the CH-EUS was compared with the histological degrees of angiogenesis and the VEGF expressions of the surgical specimens. On pathological examination, all of the intermediate high-risk GISTs expressed high levels of VEGF whereas all of the low-risk GISTs were VEGF-negative.…”
Section: Assessment Of the Malignant Potential Of The Gastrointestinamentioning
confidence: 99%
“…[61516] Recent studies have shown that this novel technique can differentiate subepithelial lesions on the basis of the pattern of contrast enhancement or by detecting intratumoral vessels, but whether or not CEH-EUS can predict the malignancy risk of GISTs remains unclear. [68121417] The aim of our study was to evaluate whether CEH-EUS findings can identify SETs and predict the malignancy risk of GISTs, in comparison with surgical pathologic findings.…”
Section: Introductionmentioning
confidence: 99%